Life Insurance Distribution Models in EU Countries - Anna SZYMAŃSKA; Teresa H. BEDNARCZYK; Jarosław SZYMAŃSKI (Communications of International Proceedings, 2021)
Research background: Dynamic technological changes and changes in consumer preferences of insurance services are prompting life insurers to change their sales strategies. However, the interest of clients in particular distribution channels of this insurance in different EU countries is not the same. The structure of life insurance distribution channels on the domestic market reflects a certain distribution model characteristic for this market. Purpose of the article: The main goal of the paper is to search for groups of EU countries with a similar level of life insurance development and a similar structure of life insurance distribution channels, and to examine whether the structure of life insurance distribution channels is in some way related to the level of development of domestic markets for this type of insurance. Methods: The empirical study was conducted on the basis of data published on the Insurance Europe and OECD websites. The level of life insurance development in EU member states was compared using three measures most often described in the literature on the subject, such as: the share of insurance companies' assets in GDP, the insurance density index (gross premium written for life insurance in the domestic market / population of the country) and the insurance penetration index (premium gross written income of life insurance in the domestic market/ GDP of the country). Two statistical methods were used to group countries, both in terms of the level of development and the structure of life insurance distribution channels: two-stage cluster analysis to determine the number of clusters and the k-means method. Own calculations were performed with the use of IBM SPSS Statistics package. Findings & Value added: The study managed to distinguish four different models of life insurance distribution in the studied countries. The type of distribution model depends primarily on the share of the agency and bancassurance channel. The differences are visible not only in the breakdown into the "Old" and "New" EU countries, but also in analyzes taking into account the level of development of the life insurance market in the studied countries. Based on the analysis, it can be concluded that the structure of life insurance distribution channels is, ceteris paribus, mainly determined by the level of development of these insurance markets. Many factors determine the model of life insurance distribution on domestic markets, which requires further detailed analyzes.
Keywords: Life Insurance; Distribution Channels; Insurance Development.